2019
DOI: 10.1021/acs.jchemed.8b00984
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Undergraduate Students’ Goals and Achievement Strategies for Laboratory Coursework

Abstract: Previous work has shown a misalignment between the goals of faculty and students for laboratory coursework. Although faculty often list learning techniques and developing critical thinking skills as goals for laboratory, students tend to focus on affective goals, such as finishing lab early and obtaining good grades. The goals of faculty have been thoroughly investigated through both qualitative and large-scale quantitative studies. However, studies on student goals for laboratory coursework have primarily bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Significance was considered at p < 0.05 (Chambers and Skinner, 2003). To quantify relationships, we applied a two-tailed Cramer's V test, where a value <0.2 indicated a weak association, 0.2 ≤ 0.3 a moderate association, and >0.3 strong association (Santos-Díaz et al, 2019). Cabell and Oelofse (2012), processed for the overall assessment of the resilience of the participating farms.…”
Section: Quantitative Datamentioning
confidence: 99%
“…Significance was considered at p < 0.05 (Chambers and Skinner, 2003). To quantify relationships, we applied a two-tailed Cramer's V test, where a value <0.2 indicated a weak association, 0.2 ≤ 0.3 a moderate association, and >0.3 strong association (Santos-Díaz et al, 2019). Cabell and Oelofse (2012), processed for the overall assessment of the resilience of the participating farms.…”
Section: Quantitative Datamentioning
confidence: 99%
“…Questioning the educational value of laboratories as part of a chemistry curriculum is a recurring theme in chemistry education, , and one that will continue to be controversial, given the challenges inherent to the determination of learning outcomes in lab courses that are closely aligned with lecture courses. However, articulation of faculty goals and expectations and the clear communication of those expected outcomes to students have been found to be an important component of the lab instruction development process. …”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, Szu and colleagues 22 found that the highestachieving students sought instructor help early. Santos-Di ́az, Hensiek, Owings, and Towns 23 surveyed undergraduate students enrolled in chemistry courses (i.e., general, physical, organic) about their goals and achievement strategies. Their results indicated that students consistently reported helpseeking as a reliable and useful strategy.…”
Section: Help-seeking and Its Benefitsmentioning
confidence: 99%